2000
DOI: 10.1046/j.1432-1327.2000.01575.x
|View full text |Cite
|
Sign up to set email alerts
|

O‐glycosylation of insulin‐like growth factor (IGF) binding protein‐6 maintains high IGF‐II binding affinity by decreasing binding to glycosaminoglycans and susceptibility to proteolysis

Abstract: Insulin-like growth factor binding protein-6 (IGFBP-6) is an O-linked glycoprotein which specifically inhibits insulin-like growth factor (IGF)-II actions. The effects of O-glycosylation of IGFBP-6 on binding to glycosaminoglycans and proteolysis, both of which reduce the IGF binding affinity of other IGFBPs were studied. Binding of recombinant human nonglycosylated (n-g) IGFBP-6 to a range of glycosaminoglycans in vitro was approximately threefold greater than that of glycosylated (g) IGFBP-6. When bound to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 47 publications
0
36
1
Order By: Relevance
“…These results suggest several potential mechanisms underlying IGFBP modulation of cell migration/invasion. IGFBP-6 does not have an RGD sequence, but it contains a heparin binding domain and so can bind to glycosaminoglycans (36). Interestingly, our previous studies investigating the role of IGFBP-6 in migration using a wound assay showed that IGFBP-6 inhibited migration in an IGF-II-dependent manner (13), which conflicts with the results presented here.…”
Section: Discussioncontrasting
confidence: 99%
“…These results suggest several potential mechanisms underlying IGFBP modulation of cell migration/invasion. IGFBP-6 does not have an RGD sequence, but it contains a heparin binding domain and so can bind to glycosaminoglycans (36). Interestingly, our previous studies investigating the role of IGFBP-6 in migration using a wound assay showed that IGFBP-6 inhibited migration in an IGF-II-dependent manner (13), which conflicts with the results presented here.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, despite their homogeneity, the IGFBPs appear to possess genuine differences in their response to GAGs: IGFBPs-3, -5 and -6 all show a reduced affinity for IGFs following GAG exposure, whereas the ligand affinity of IGFBP-4 appears to be unaffected. Data on IGFBP-2 are contradictory, but at least in some settings, IGFBP-2 has been reported to bind GAGs only in the presence of IGFs, while IGFBP-1 does not bind GAGs at all (23)(24)(25). Finally, GAGs appear to exert a larger impact on the binding of ALS to preformed complexes of IGF-I and IGFBP-3 than on the binding of IGF-I to IGFBP-3 (14).…”
Section: Discussionmentioning
confidence: 98%
“…However, both options appear to exist. The proximity of the HBD and the binding sites for IGF and ALS may explain that several different GAGs are reported to affect IGF:IGFBP as well as IGFBP-3:ALS complex formation (13,14,(22)(23)(24)(25). Interestingly, despite their homogeneity, the IGFBPs appear to possess genuine differences in their response to GAGs: IGFBPs-3, -5 and -6 all show a reduced affinity for IGFs following GAG exposure, whereas the ligand affinity of IGFBP-4 appears to be unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…7,40 Presumably, these multifunctional roles for IGFBP-3 are influenced by posttranslational modifications and susceptibility to proteases. 8,13,23,33 In addition to IGF-I, several other molecules such as interleukin-1, tumor necrosis factor-a, transforming growth factor-b (TGFb), retinoic acid, as well as the PI3K/AKT and MAPK/ERK1/2 pathways have been implicated in the regulation of IGFBP-3 expression. 12,40,48 The overexpression of some IGFBP isoforms has been well documented in gliomas, in particular, glioblastoma (GBM).…”
mentioning
confidence: 99%